Immunologic Biomarkers for Clinical and Therapeutic Management of Psoriasis. (20th July 2014) - Cordiali-Fei, P.; Bianchi, L.; Bonifati, C.; Trento, E.; Ruzzetti, M.; Francesconi, F.; Bultrini, S.; D'Agosto, G.; Bordignon, V.; Francavilla, V.; Tripiciano, A.; Chiricozzi, A.; et al.
Abstract : Background . The therapeutic management of psoriasis includes conventional treatments as well as the new generation of highly effective TNF- α inhibitors. However, psoriasis has proven to be a complex therapeutic challenge and treatment failures are not uncommon. Thus, laboratory biomarkers of disease progression/therapeutic efficacy may greatly help in the clinical management of psoriasis. Aims . To identify laboratory biomarkers for clinical management and therapeutic monitoring of psoriasis. Methods . An observational study performed on 59 patients, presenting moderate to severe psoriasis, undergoing treatment with anti-TNF- α agents (etanercept, adalimumab, and infliximab). Soluble and cellular immune/inflammatory parameters were assessed at baseline and after 12 and 24 weeks of treatment. Results . Clinical efficacy was achieved in 88% of the subjects at 12 weeks, reaching 90% after 24 weeks. IL-6 and IL-22, which were elevated at baseline, were significantly reduced, in association with a significant decrease of CLA+ T cells and an increase of Treg lymphocytes. T, B, and NK cell subsets and T cell response to recall antigens did not show any evidence of immune suppression. Conclusions . Immune/inflammatory parameters including IL-6 and IL-22, CLA+ T cells, and Treg lymphocytes may prove to be valuable laboratory tools for the clinical and therapeutic monitoring of psoriasis.